2018
DOI: 10.1007/s10157-018-1565-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and its severity in children with steroid sensitive nephrotic syndrome during remission

Abstract: There is high incidence of hypertension in NS children during remission. Though significant positive correlation was found with positive family history of hypertension and deranged lipid profile highlighting possibility of essential hypertension in them, there is need for close active monitoring and management of hypertension in them as untreated cases may have significant target organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The reported prevalence of hypertension in childhood SSNS is variable between 7 and 34% [195][196][197][198][199][200]. It occurs in children with SDNS and FRNS [200] and also in children in remission and/or 1-10 years off medication [196], especially in case of positive family history [195,196].…”
Section: Management Of Severe Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of hypertension in childhood SSNS is variable between 7 and 34% [195][196][197][198][199][200]. It occurs in children with SDNS and FRNS [200] and also in children in remission and/or 1-10 years off medication [196], especially in case of positive family history [195,196].…”
Section: Management Of Severe Edemamentioning
confidence: 99%
“…The reported prevalence of hypertension in childhood SSNS is variable between 7 and 34% [195][196][197][198][199][200]. It occurs in children with SDNS and FRNS [200] and also in children in remission and/or 1-10 years off medication [196], especially in case of positive family history [195,196]. The etiology is multifactorial and includes medication side effects, in particular gluco-corticoids and CNIs, and fluid overload due to inappropriate use of albumin infusion during relapses.…”
Section: Management Of Severe Edemamentioning
confidence: 99%
“…Of those, 73% had a positive family history of HTN compared to 32% in the normotensive group. BP was significantly correlated with serum cholesterol and LDL levels (10).…”
Section: Epidemiologymentioning
confidence: 99%
“…Previous studies have identified, and attempted to characterize, hypertension in both pediatric and adult patients with NS. [2][3][4]8,9 Cameron et al noted significantly elevated BP measurements in 31% of patients older than 15 years of age in their study of minimal change disease, 10 and this seemed to coincide with the proteinuric state. In addition, between 10% and 30% of pediatric patients with steroid-resistant NS, or genetic forms of NS, were hypertensive on presentation on analysis of the PodoNet registry data.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, they may develop increased arterial blood pressure (BP) throughout the course of NS. 2 , 3 , 4 Blood pressure lability has been observed in these cohorts of pediatric patients with variable degrees of proteinuria; however, the impact of proteinuria on BP is not fully elucidated. 2 , 3 , 4 Clarifying this further may impact therapeutic approaches for hypertension in patients with proteinuria, even if it is only transient.…”
Section: Introductionmentioning
confidence: 99%